About structure and waves with laureates : HISK 2012 - Hug, Cathérine; Schafhausen, Nicolaus; HISK, Gent (Gent : HISK, 2012)
Boogaerts, Line ; Buklys, Liudvikas ; Coucke, Joachim ; De Mont, Alice ; Epnere, Ieva ; Föllings, Paulien ; Kuilboer, Conny ; Leddington, Gary ; Noonan, Clare ; Pain, Odilon ; Rödiger, Daniel
Published in conjunction with the exhibition 'About waves and structure, behavior, disagreement, confidence and pleasure' at the HISK at Gent, 17.11.2012-09.12.2012
boek